Small nucleolar RNAs and their genes in vertebrates - Makarova, J. A; Kramerov, D. A (Russian journal of genetics, 2010)
Genes of box C/D small nucleolar RNAs (snoRNAs) were searched for in the genomes of members of all classes of vertebrates that do not belong to placental mammals. A tendency for an increase in the number of copies of snoRNA genes was observed in such vertebrates. This trend was most pronounced in anamnia (amphibians and fish). Box C mutations were found in 14 snoRNAs in all gene copies among all species studied. The role of the described events is discussed.